(untitled) (Global Journal of Medical Research, 2019)
Atypical femoral fractures (AFFs) are defined as atraumatic fractures of the femoral diaphysis and are known to be a complication of prolonged bisphosphonate (BP) therapy. Surgical treatment of AFFs consists of intramedullary (IM) nailing. We report the case of a 58year-old female patient who presented with bilateral femoral fractures after 12 years of BP therapy. Surgical management using IM nails resulted in iatrogenic fractures of the femoral shaft in both limbs. We therefore, opted for conservative treatment, where a non-weight bearing protocol was implemented. Healing was then observed after six months of follow-up.